Pengaruh Media Pembelajaran Kotak Ajaib Dalam Meningkatkan Numerasi Peserta Didik Kelas I Madrasah Ibtidaiyah - Eka Zaqiya Rahmawati; Ria Resti Fauziah; Rahmat Rudianto (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of magic box learning media on the numeracy skills of first-grade students at MI Al-Azhar Menganti. This study used a quantitative approach using the true experimental design method and a pretest-posttest control group design. This study was conducted in the experimental and control classes. The results showed that the use of magic boxes was in the